2007
DOI: 10.1111/j.1365-3040.2007.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine accumulation is more effective in chloroplasts than in the cytosol for protecting transgenic tomato plants against abiotic stress

Abstract: Tomato (Lycopersicon esculentum Mill. cv. Moneymaker) plants were transformed with a gene for choline oxidase (codA) from Arthrobacter globiformis. The gene product (CODA) was targeted to the chloroplasts (Chl-codA), cytosol (Cyt-codA) or both compartments simultaneously (ChlCyt-codA). These three transgenic plant types accumulated different amounts and proportions of glycinebetaine (GB) in their chloroplasts and cytosol. Targeting CODA to either the cytosol or both compartments simultaneously increased total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 41 publications
4
73
0
1
Order By: Relevance
“…It is possible that different plant species have different capacities for cytosolic choline biosynthesis and transport to the chloroplast for GB biosynthesis. COD-transgenic tomato plants accumulated more GB in the cytosol than the chloroplast, similar to CMO-tobacco (Park et al 2007a). This indicates that both tobacco and tomato plants are less efficient at either choline biosynthesis and/or its transport to the chloroplast.…”
Section: Factors Affecting Gb Accumulation In Transgenic Plantsmentioning
confidence: 90%
See 3 more Smart Citations
“…It is possible that different plant species have different capacities for cytosolic choline biosynthesis and transport to the chloroplast for GB biosynthesis. COD-transgenic tomato plants accumulated more GB in the cytosol than the chloroplast, similar to CMO-tobacco (Park et al 2007a). This indicates that both tobacco and tomato plants are less efficient at either choline biosynthesis and/or its transport to the chloroplast.…”
Section: Factors Affecting Gb Accumulation In Transgenic Plantsmentioning
confidence: 90%
“…High concentration of intracellular ROS has damaging effects on cellular components and also hinders repair of the PSII complex by inhibition of de novo protein synthesis (Nishiyama et al 2001). Park et al (2007a) suggested that one of the possible reasons for the greater protection against low-temperature stress in chloroplast-targeted CODtransgenic tomato plants might be an improved oxygenevolving ability of the PSII complex by GB-induced repair. Another reason might be that GB stabilizes membrane integrity against extreme temperatures, reduces membrane lipid peroxidation, and protects PSII electron transport Hamilton and Heckathorn 2001).…”
Section: Effect Of Gb On Low Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…in higher plants. Glycinebetaine (GB) is one such osmolyte whose association with tolerance to abiotic stresses has been supported by a number of publications (Manaf, 2016;Wang et al, 2010;Park et al,2007).The researches on manipulation of GB biosynthetic pathway by genetic transformation and exogenous application are in continuous progress. However, exogenousfoliar application of GB represents a short and simple approach for mitigating the adverse effects of stress.…”
Section: Issn: 2319-7706 Volume 7 Number 07 (2018)mentioning
confidence: 99%